Determinants of intention and behaviorof responsible consumption through reduce waste generation in Thailand - Aumeboonsuke, Vesarach (NIDA Development Journal, 2024)
The purpose of this research was to investigate the determinants of intention and behavior of responsible consumption through reduce waste generation in Thailand. Reduce waste generation is one of the targets under Sustainable Development Goal 12 (SDG12), responsible consumption and production. The four components in reducing waste generation under this study are prevention, reduction, recycling, and reuse. An analysis was conducted by employing the theory of planned behavior (TPB) model that examined associations among attitude, subjective norms, perceived behavioral control, intention, and behavior. Additionally, knowledge about waste management was included in the TPB. The results were obtained based on the survey data from 174 participants in Thailand during May 2023. Partial least squares structural equation modeling (PLS-SEM) was employed to examine the path associations between each variable in the research framework. The evidence from this study was beneficial to understand how the intention and behavior of Thai people toward reduce waste generation are determined by attitude, subjective norms, perceived behavioral control, and households’ knowledge on waste management. More importantly, it was beneficial for policy makers to form optimal strategies aimed to promote the intention and behavior to reduce waste generation and to further achieve responsible consumption under SDG12.